Pengaruh Perubahan Tutupan Lahan terhadap Pola Banjir di Ibu Kota Provinsi Lampung: Studi Menggunakan SIG dan Pendekatan Temporal - Matondang, Pebriadi Halomoan; Rizkiani, Deli; Akbari, Irgi; Haerudin, Nandi; Mulyasari, Rahmi (OPHIOLITE: Jurnal Geologi Terapan, 2024)
Bandar Lampung often faces major challenges related to flooding. In recent years, flooding in the city has become a serious problem that requires special attention and handling. Infrastructure development and continuous population growth affect changes in the city's environmental setting. From the continuous flooding in Bandar Lampung city, it is necessary to analyse flood patterns with a spatial and temporal approach. The utilization of Geographic Information System (GIS) method is one of the effective ways in making maps with various data used such as rainfall, land cover, watershed, slope, and information on flood incidents over a 10-year period, from 2013 to 2023. The watershed, land cover and slope data also provide an overview of the dynamics of water flow and its influence on flood-prone areas. From the data, it was found that the distribution of Bandar Lampung urban forest area decreased by 63859.61 ha from 83778.11 ha to 19918.5 ha or about 23.8% of the Bandar Lampung City area. In addition, there was an increase in residential and industrial areas of 36750.95 ha from 2013 of 27143.83 ha to around 63,894.78 ha or approximately 76.2% of the total area of Bandar Lampung City. This research contributes to the importance of understanding the dynamics of flooding in Bandar Lampung City and contributes to the understanding of the dynamics of flooding in Bandar Lampung City.